CHRONIC KIDNEY DISEASE IN DOGS AND CATS: STAGING APPROACH IN SCIENTIFIC LITERATURE (REMUNOM, 2025)
Chronic Kidney Disease (CKD) in dogs and cats is characterized by structural and/or functional renal alterations persisting for three months or more, resulting in progressive and irreversible loss of glomerular filtration rate. This work reviews the main physiological aspects of the renal system, the multifactorial etiology of CKD, diagnostic methods, clinical manifestations, and staging criteria according to the guidelines of the International Renal Interest Society (IRIS). The importance of laboratory markers such as creatinine, urea, and SDMA, as well as the evaluation of proteinuria and systemic blood pressure, is highlighted for early diagnosis and monitoring of disease progression. Individualized therapeutic recommendations for each stage are addressed, including nutritional management, hypertension control, correction of electrolyte disturbances, and vitamin supplementation, aiming to slow CKD progression and promote better quality of life for patients. The study emphasizes the need for continuous monitoring and professional updating for an efficient and evidence-based approach in small animal clinical practice.